Patient-derived and gene-edited pluripotent stem cells lacking NPHP1 recapitulate juvenile nephronophthisis in abnormalities of primary cilia and renal cyst formation - Arai, Yutaka; Ito, Hidenori; Shimizu, Tomoya; Shimoda, Yuzuno; Song, Dan; Matsuo-Takasaki, Mami; Hayata, Tadayoshi; Hayashi, Yohei (Frontiers in Cell and Developmental Biology, 2024)
Juvenile nephronophthisis is an inherited renal ciliopathy with cystic kidney disease, renal fibrosis, and end-stage renal failure in children and young adults. Mutations in the NPHP1 gene encoding nephrocystin-1 protein have been identified as the most frequently responsible gene and cause the formation of cysts in the renal medulla. The molecular pathogenesis of juvenile nephronophthisis remains elusive, and no effective medicines to prevent end-stage renal failure exist even today. No human cellular models have been available yet. Here, we report a first disease model of juvenile nephronophthisis using patient-derived and gene-edited human induced pluripotent stem cells (hiPSCs) and kidney organoids derived from these hiPSCs. We established NPHP1-overexpressing hiPSCs from patient-derived hiPSCs and NPHP1-deficient hiPSCs from healthy donor hiPSCs. Comparing these series of hiPSCs, we found abnormalities in primary cilia associated with NPHP1 deficiency in hiPSCs. Kidney organoids generated from the hiPSCs lacking NPHP1 formed renal cysts frequently in suspension culture with constant rotation. This cyst formation in patient-derived kidney organoids was rescued by overexpression of NPHP1. Transcriptome analysis on these kidney organoids revealed that loss of NPHP1 caused lower expression of genes related to primary cilia in epithelial cells and higher expression of genes related to the cell cycle. These findings suggested the relationship between abnormality in primary cilia induced by NPHP1 loss and abnormal proliferative characteristics in the formation of renal cysts. These findings demonstrated that hiPSC-based systematic disease modeling of juvenile nephronophthisis contributed to elucidating the molecular pathogenesis and developing new therapies.